W.T. Harris, Peirce, and the Charge of Nominalism. Issue 2 (October 2015) - Agler, David W.; Stango, Marco
Abstract : While a number of classical pragmatists crafted their philosophies in conjunction with a careful study of Hegel's works, others saw their philosophies emerge in antagonism with proponents of Hegel. In this paper, we offer an instance of the latter case. Namely, we show that the impetus for Charles S. Peirce's early articulation and avowal of realism (the claim that some generals are real) was William Torrey Harris's claim that the formal laws of logic lacked universal validity. According to Harris, the leading representative of Hegelism in the United States, the universal validity of the laws of logic rested on a nominalistic metaphysics that a Hegelian-realism showed to be false. In response to this charge, we articulate how Peirce's attempt to prove the universal validity of the laws of logic resulted in avowing a realism that differed from both nominalism and Harris's Hegelian-realism.